Frontal sinus obliteration with iliac crest bone grafts - Monnazzi, M.; Gabrielli, Mário Francisco Real [UNESP]; Gabrielli, Marisa Aparecida Cabrini; Vieira, Eduardo Hochuli [UNESP]; Pereira Filho, Valfrido Antonio [UNESP] (Elsevier, 2011)
This study evaluated postoperative results of 8 cases of frontal sinus fractures treated by frontal sinus obliteration with autogenous bone from the anterior iliac crest.